A novel room-temperature formaldehyde gas sensor based on walnut-like WO3 modification on Ni–graphene composites - Mehmood, Shahid; Khan, Faheem Ullah; Shah, Muhmmad Naeem; Ma, Junxian; Yang, Yatao; Li, Guijun; Xu, Wei; Zhao, Xiaojin; He, Wei; Pan, Xiaofang (Frontiers in Chemistry, 2022)
Ternary composite with great modulation of electrons transfer has attracted lots of attentions from the field of high-performance room temperature (RT) gas sensing. Herein, walnut-like WO3-Ni-Graphene ternary composites were successfully synthesized by the hydrothermal method for formaldehyde (HCHO) sensing at RT. The structural and morphological analysis were carried out by scanning electron microscope (SEM), transmission electron microscopy (TEM), X-ray diffraction (XRD), Raman spectroscopy and X-ray photoelectron spectroscopy (XPS). SEM and TEM studies confirmed that walnut-like WO3 nanostructures with average size of 53±23 nm were functionalized. Raman and XPS results revealed that due to deformation of O-W-O lattice, surface oxygen vacancies Ov and surface adsorbed oxygen species Oc were present. Gas sensing measurement shows that response of WO3-Ni-Gr composite (86.8%) was higher than Ni-Gr composite (22.7%) for 500 ppm HCHO at RT. Gas sensing enhancement can be attributed to p-n heterojunction formation between WO3 and Ni-Gr, Oc, spill-over effect of Ni decoration and special walnut-like structure. Moreover, long term stability (%R = 61.41 ± 1.66) for 30 days and high selectivity in presence of other gases against HCHO, suggested that the proposed sensor could be an ideal candidate for future commercial HCHO sensing in real environment.